Implikasi Pemisahan Pemilu Nasional dan Daerah - M. Iwan Satriawan (PRANATA HUKUM, 2012)
Election in Indonesia have been conducted since 1955 that continue in the new order era from 1971 until 1997, after the fall election the new order in the transition era of reform has been carried out 3 times, from 1999 to 2009. But until now, local issues did not really resonate despite the existence of this DPD caused united between national and local elections so that local issues covered by the dominance of national issues.